Analisis del régimen jurídico de los alimentos, en cuanto a los obligados a la prestación abuelos/as como alimentante subsidiario, cancele facultativamente las pensiones alimenticias - Armijos Vega, Jhon Alexander (2019)
The present thesis of degree deals with the title: "ANALYSIS OF THE FOOD LEGAL REGIME, AS TO THE OBLIGORS TO THE BENEFIT GRANDPARENT / AS SUBSIDIARY FEEDER, CANCELS THE FOOD PENSIONS IN A FACULTY" I consider as a general objective, to carry out a study doctrinal and legal conceptualization of grandparents as elders and subsidiary nurturers have only facultative obligation. In order to achieve this goal I made use of several methods which were applied to the process such as: inductive, deductive, historical, comparative, statistical, analytical, etc. As well as the application of some techniques such as: the surveys in which I asked 5 questions to 30 legal professionals as experts on the subject, from which I obtained great results, such as that the elderly grandparents live mostly in precarious situations. it makes it difficult for them to comply with this imposed obligation, that this obligation should be imposed first by verifying the economic resources they have and in an optional way so as not to violate the right to a dignified life that all people enjoy. With the fieldwork, it has allowed me to reach well-founded, clear and precise criteria, with a very important bibliography that helped the verification of objectives, development of both the conclusions and the recommendations and as a basis for proposing a reform proposal with which I intend to contribute with the changes formulated a solution to the problem.